Implantable Cardiac Defibrillators and Sudden Death in Recent Onset Nonischemic Cardiomyopathy: Results From IMAC2 - Sheppard, Richard; Mather, Paul J.; Alexis, Jeffrey D.; Starling, Randall C.; Boehmer, John P.; Thohan, Vinay; Pauly, Daniel F.; Markham, David W.; Zucker, Mark; Kip, Kevin E.; McNamara, Dennis M. (Journal of cardiac failure, 2012)
Given the potential for recovery in recent onset nonischemic cardiomyopathy (ROCM), the timing and need for implantable cardioverter-defibrillator (ICDs) remains controversial. We examined the utilization of ICDs and the impact on survival for subjects with ROCM. An National Heart, Lung, and Blood Institute sponsored registry enrolled 373 subjects with ROCM, all with a left ventricular ejection fraction (LVEF) ≤0.40 and ≤6 months of symptoms. The mean age was 45 ± 14 years, 38% were female, 21% black, 75% New York Heart Association II/III, and the mean LVEF was 0.24 ± 0.08. Survival was comparable for subjects with an ICD within 1 month of entry (n = 43, 1/2/3 year % survival = 97/97/92) and those with no ICD at 1 month (n = 330, % survival = 98/97/95, P = .30) and between those with and without an ICD at 6 months (ICD, n = 73, 1/2/3 year % survival = 98/98/95; no ICD, n = 300, % survival = 98/96/95, P = .95). There were only 6 sudden cardiac deaths (SCD) noted (% survival free from SCD = 99/98/97) and these occurred in 1.9% of subjects without ICD and 0.9% of those with a device (P = .50). In a multicenter cohort of ROCM the risk of SCD was low at 1% per year. Early ICD placement did not impact survival and can be deferred while assessing potential for myocardial recovery.